A dose-ranging study of the physiological and self-reported effects of repeated, rapid infusion of remifentanil in people with opioid use disorder and physical dependence on fentanyl - Lile, Joshua A.; Shellenberg, Thomas P.; Babalonis, Shanna; Hatton, Kevin W.; Hays, Lon R.; Rayapati, Abner O.; Stoops, William W.; Wesley, Michael J. (Psychopharmacology, 2024)
Rationale Understanding mechanisms of drug use decisions will inform the development of treatments for opioid use disorder (OUD). Decision-making experiments using neurobehavioral approaches require many trials or events of interest for statistical analysis, but the pharmacokinetics of most opioids limit dosing in humans. Objectives This experiment characterized the effects of repeated infusions of the ultra-short acting opioid remifentanil in people with OUD and physical opioid dependence. Methods An inpatient study using a within-subjects, single-blind, escalating, within-session, pre-post design was conducted. Seven (3 female) subjects were maintained on oral oxycodone (40–60 mg, 4x/day = 160–240 total mg/day) for seven days prior to the dose-ranging session. Subjects received infusions of three ascending remifentanil doses (0.03, 0.1, 0.3 mcg/kg/infusion in 2 subjects; 0.1, 0.3, 1.0 mcg/kg/infusion in 5 subjects) every minute for 40 min per dose, with infusions administered over 5 s to model naturalistic delivery rates. End tidal carbon dioxide, respiration rate, oxygen saturation (SpO 2 ) and heart rate were measured continuously. Blood pressure (BP), pupil diameter and self-reported drug effects were measured every 5 min. Results Pupil diameter, SpO 2 and systolic BP decreased, and ratings on prototypic subjective effects questionnaire items increased, as a function of remifentanil dose. The number of infusions held because of sedation or physiological parameters exceeding predetermined cutoffs also increased with dose. Conclusions This experiment established doses and procedures for the safe delivery of rapid, repeated remifentanil infusions to individuals with OUD and physical fentanyl dependence, which can be applied to the mechanistic study of opioid use decisions.